East Asian summer monsoon variations during the last deglaciation, recorded from a stalagmite at Linyi, northern China. (15th January 2018) - Li, Qian; Li, Guangxue; Chen, Min-Te; Cheng, Hai; Xu, Jishang; Ding, Dong; Ma, Yanyan; Qiao, Lulu; Zhang, Qiang; Zhang, Yang; Wang, Haoyin; An, Zhenzhen; et al.
Abstract: A 230 Th-dated stalagmite record from Linyi, Shandong Province, provides a detailed history of the East Asian summer monsoon (EASM) in northern China during the last deglaciation. Our record reveals changes that are similar to previously published stalagmite records from the East Asian monsoon region on centennial and millennial scales, although some subtle and detail discrepancies are observed. Comparisons with other paleoclimate records show that the EASM was jointly controlled by the North Atlantic climate and low-latitude tropical processes during the last deglaciation. Ocean-atmospheric interactions, particularly sea surface temperature changes in the tropical Pacific might have contributed to the increasing trend of the EASM during the Bølling-Allerød and to the lesser weakening in the EASM during the Younger Dryas. In addition, the significantly higher growth rates of the stalagmite during the Heinrich Event 1 might have been driven by the CO2 degassing processes. Future studies with long-term monitoring of the calcite deposition rate at this site will be needed to support our arguments on the CO2 degassing processes.